Assessing the Socioeconomic Consequences of Climate-Induced Migration in Southeast Asia - Devi Anggraini (Mahogany Journal De Social, 2024)
This research aims to evaluate the social and economic impacts of migration triggered by climate change in Indonesia, with a focus on Central Kalimantan, South Sumatra and East Java. Research methods involve case studies, in-depth interviews, and Focus Group Discussions (FGD) to obtain comprehensive data from migrants and host communities. The results show that migrants often experience social isolation and difficulties in integrating into local communities, while host communities face social tensions and increased burdens on basic services. Economically, migrants experience difficulties in finding suitable work and face rising living costs. These findings highlight the need for better support for migrants, improved infrastructure and social services in host communities, and the development of more responsive and evidence-based migration policies. In conclusion, a holistic approach involving multiple stakeholders is essential to effectively manage the impacts of migration, support social integration, and improve economic well-being in affected regions.